Degradation of well cement in HPHT acidic environment: Effects of CO2 concentration and pressure. (November 2016) - Omosebi, Omotayo; Maheshwari, Himanshu; Ahmed, Ramadan; Shah, Subhash; Osisanya, Samuel; Hassani, Shokrollah; DeBruijn, Gunnar; Cornell, Winton; Simon, Dave
Abstract: Application of cement in high-pressure high-temperature (HPHT) carbonic acid containing environment poses serious well integrity issues. HPHT condition facilitates acid attack on well cement resulting in the loss of structural integrity. This paper presents the results of an experimental study conducted to investigate the effects of CO2 concentration (mole fraction) and pressure on mechanical integrity of degraded Classes G and H cements after exposure to carbonic acid environment. Cement cores were prepared and aged in autoclave filled with 2% NaCl solution saturated with mixture of methane and carbon dioxide gases for durations up to 28 days. Experiments were performed by varying test pressure and CO2 concentration. Compressive strength, porosity and permeability of unaged and aged samples were measured to assess the level of degradation. Besides, analysis of the mineralogy, the microstructure, and the morphology of specimens was conducted. After exposure, incomplete hydration of clinker materials, carbonation of cement hydrates, leaching of by-products of carbonation, and structural transformation of amorphous calcium silicate hydrate to its crystalline form were observed. Generally, compressive strength increased with CO2 concentration due to carbonation of calcium hydroxide (CH) and calcium silicate hydrate (C-S-H). Correspondingly, porosity and permeability decreased. Furthermore, degree of degradation is greatly influenced by pressure.